Effects of Mitophagy on Regulatory T Cell Function in Patients With Myasthenia Gravis - Wang, Na; Yuan, Jiang; Karim, Md Rezaul; Zhong, Ping; Sun, Yan-Peng; Zhang, Hong-Yan; Wang, Yun-Fu (Frontiers in Neurology, 2020)
Objective: This study was conducted to determine whether regulatory T cells (CD4+CD25+T, Tregs) show abnormal mitophagy as well as the function of Tregs in patients with myasthenia gravis (MG). Methods: CD4+T cells and CD4+CD25+Treg cells were obtained from 15 patients with MG (MG group) and 15 controls (N group). Tregs from the MG group were subjected to rapamycin-induced culture for 48 h (Rapa group) and 3-methyladenine-induced culture for 48 h (3-MA group). The levels of mitophagy in Tregs were then observed through electron and confocal microscopy. Expression of the autophagy-related protein LC3-II was detected by western blotting, and mitochondrial function in each group was evaluated by flow cytometry. Inhibition of Treg cell proliferation was detected by flow cytometry. Results: Mitophagy in the MG group was lower than that in the N group; it was higher in the Rapa group compared to that in the MG group and lowered in the 3-MA group than in the MG group. Expression of the autophagy-related protein LC3-II was lower in the MG group than in the N group, higher in the Rapa group than in the MG group, and lower in the 3-MA group than in the MG group. The mitochondrial membrane potential was lower in the MG group compared to that in the N group; it was higher in the Rapa group than in the MG group and lowered in the 3-MA group than in the MG group. Inhibition of Treg proliferation was lower in the MG group than in the N group; it was higher in the Rapa group than in the MG group and lowered in the 3-MA group than in the MG group. Conclusion: The decreased mitochondrial membrane potential and mitophagy in Tregs in the MG group may be related to a decreased inhibition of Treg proliferation. The mitochondrial membrane potential was increased after adding the autophagy agent Rapa to enhance mitophagy, and the proliferation inhibition function of Tregs was also enhanced. The autophagy agent 3-MA down-regulated mitophagy, which decreased the mitochondrial membrane potential and inhibitory effect of Tregs. These results reveal the possible cellular immune mechanism of Treg dysfunction in MG.